Intravascular Imaging-Guided Percutaneous Coronary Intervention in Patients With End-Stage Renal Disease on Maintenance Dialysis - Chia-Pin Lin, MD; Fu-Chih Hsiao, MD; Ying-Chang Tung, MD; Tzyy-Jer Hsu, MD; Shing-Hsien Chou, MD; Yu-Sheng Lin, MD; Shao-Wei Chen, MD, PhD; Pao-Hsien Chu, MD (JACC: Asia)
Background: Patients with end-stage renal disease (ESRD) are at a higher risk of cardiovascular diseases. Intravascular imaging (IVI)-guided percutaneous coronary intervention (PCI) using optical coherence tomography (OCT) or intravascular ultrasound (IVUS) has been shown to result in better clinical outcomes than angiography guidance. Nevertheless, the clinical outcomes of IVI-guided PCI in ESRD patients remain uncertain. Objectives: This study aimed to compare the clinical outcomes of OCT- and IVUS-guided PCIs in ESRD patients and to report the trend of IVI-guided PCI in Taiwan. Methods: Patients with ESRD on maintenance dialysis, who underwent OCT- or IVUS-guided PCI from 2015 to 2021, were compared by propensity-score matching. The primary outcome was composite cardiovascular outcomes, including coronary revascularization, cardiovascular death, and acute myocardial infarction. Results: In 2021, IVI was used to guide PCIs in 27% (15,613 of 57,845) of general and 27.5% (1,754 of 6,387) of ESRD patients. Among 4,759 eligible ESRD patients, 443 and 4,316 patients underwent OCT- and IVUS-guided PCIs, respectively. After matching, the incidence of the primary outcome was comparable between the OCT and IVUS groups (42.1 [95% CI: 36.2-48.0] vs 47.6 [95% CI: 43.0-52.2] events per 100 person-years; HR: 0.88; 95% CI: 0.74-1.06). The results were similar for all components of the primary outcome and in subgroup analyses. Conclusions: The number of PCI- and IVI-guided procedures has progressively increased in the past decade in Taiwan in both the general and ESRD populations. Among ESRD patients on maintenance dialysis, the clinical outcomes were comparable between OCT- and IVUS-guided PCI.